International Bibliometric Analysis of Literature on Intrauterine Insemination - Septriani, Nur Indah; Paramita, Pradnya; Firdiana, Vykra Aulia; Norfita, Tia Silva; Sayidinar, Aisha (RUMPHIUS, 2025)
Intrauterine insemination (IUI) is an artificial insemination method that employs specialized devices to introduce spermatozoa into the uterus. IUI is utilized to address challenges associated with poor reproductive outcomes and to optimize the productivity of livestock. Consequently, its application and utilization has gained global attention and is being continuously developed. Therefore, this study aimed to analyze the global literature on intrauterine insemination research over the preceding decade. Documents related to intrauterine insemination research were presented in the results of a bibliometric study indexed in the Scopus database for the period 2012–2022. On a global scale, the total number of identified documents amounted to 2,721, with an average annual production of 272 documents. Ten countries worldwide were identified as leading contributors to research publications on intrauterine insemination, including the United States with the most document production (n=643), followed by Turkey (n=175), India (n=173), China (n=161), United Kingdom (n=159), Iran (n=153), Netherlands (n=152), Canada (n=140), France (n=131), and Italy (n=129). This study of novelty comprehensive bibliometric analysis to map a decade of global research trends in intrauterine insemination across both human and animal applications. Unlike previous narrative reviews that focused on clinical or technical aspects, this research highlights global collaboration networks, publication dynamics, and emerging thematic hotspots within the IUI domain. Publications related to intrauterine insemination showed an upward trajectory from 2012 until 2021, followed by a decline in 2022. The findings from this analysis provide valuable guidance for future research in the field of intrauterine insemination.